Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675223
|View full text |Cite
|
Sign up to set email alerts
|

Hacking Culture, Not Devices

Abstract: This paper examines the motivations, activities, and ideals of people organizing feminist hackerspaces: collaborative workspaces developed to support women's creative and professional pursuits. Drawing on interviews, participant observation and archival data collected across the Pacific Northwest over nine months, we show how members of these spaces use small-scale collaborative design and acts of making to work out their place in society in ways that contest widely accepted understandings of hacking, technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(40 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…This could indicate that while they are very strong in terms of a classic normative democratic sense of participation, they are actually quite weak in terms of whether they enhance a sense of educative dividend, or a collective experience of participation mediated by metrics or collective communication. This perhaps confirms some of the literature emerging around free and open source software, hackerspaces, and the politics of openness that directly challenge the notion of openness, or suggest that forms of exclusion (especially gendered exclusion) remain persistent and troubling in these communities (Dunbar-Hester 2014;Nafus 2012;Ford and Wajcman 2017;Fox, Ulgado, and Rosner 2015).…”
Section: Political Autonomy Vs Educative Dividendsupporting
confidence: 69%
“…This could indicate that while they are very strong in terms of a classic normative democratic sense of participation, they are actually quite weak in terms of whether they enhance a sense of educative dividend, or a collective experience of participation mediated by metrics or collective communication. This perhaps confirms some of the literature emerging around free and open source software, hackerspaces, and the politics of openness that directly challenge the notion of openness, or suggest that forms of exclusion (especially gendered exclusion) remain persistent and troubling in these communities (Dunbar-Hester 2014;Nafus 2012;Ford and Wajcman 2017;Fox, Ulgado, and Rosner 2015).…”
Section: Political Autonomy Vs Educative Dividendsupporting
confidence: 69%
“…According to the report and other research, women have indicated that collaboration and community building is a key motivator in their desire to "make" (Bean, Farmer & Kerr, 2015;Fox, Ulgado & Rosner, 2015;Intel, 2014). Simultaneously, one of the barriers to women's participation in STEM careers and making is the lack of mentorship (Intel, 2014).…”
Section: Gendermentioning
confidence: 99%
“…Therefore, incorporating workshops or projects that require collaboration, address a social need, solve a problem, and/or is project focused may help to engage more women. In terms of what is produced through "making, " women are more likely to access making through arts and crafts (Fox et al, 2015;Intel, 2014). Thus, higher female participation could be encouraged by offering workshops, projects or materials that allow for multiple access points to creation, such as, sewable or paper electronics and circuits.…”
Section: Gendermentioning
confidence: 99%
“…Thus, given those challenges, Buechley's success in "hacking" the Arduino in ways that increased female participation is all the more significant, and surely counts as one tool in the "directed mutation" portfolio. But equally important is what Fox et al (2015) refer to as "hacking gender". In their study of gender diversity in physical hackerspaces, they noted that excluding all males was a relatively rare strategy.…”
Section: Arduino: a Case Study In Generative Justicementioning
confidence: 99%